First study of the Polycladida (Rhabditophora, Platyhelminthes) from the Pacific Coast of Costa Rica - Soutullo, Patricia; Cuadrado, Daniel; Noreña, Carolina (Zootaxa, 2021)
In the present work was carried out in the intertidal zone of Las Baulas de Guanacaste National Marine Park (PNMB) located on the Pacific coast of Costa Rica.                The main objective was to contribute to knowledge about the invertebrate diversity of the park, one of the richest bioregions on the planet, about which little is known. This study assesses the Order Polycladida Lang, 1884, a cornerstone of this ecosystem and one of the most cosmopolitan and plastic invertebrate taxa in the animal kingdom.                In total, 57 individuals were collected in the rocky intertidal zone of Carbón and Langosta beaches. Nine different species were identified, of which four are new for Costa Rica: Semonia bauliensis n. sp.; Cryptostylochus sesei n. sp.; Paraplanocera angeli n. sp., Prostheceraeus fitae n. sp.; and five new records: Paraplanocera oligoglena (Schmarda, 1859); Marcusia ernesti Hyman, 1953; Enchiridium magec Cuadrado, Moro & Noreña, 2017; Pseudobiceros bajae (Hyman, 1953); and the genus Boninia spp.